Management of organic orchard: Effect of vermicompost on fruit yield of ber (Zizyphus mauritiana Lamk.) cv. Seo and soil health in Central India - Kumar, Sudhir; Prasad, Rajendra; Shukla, Ashok; Dev, Inder; Chaturvedi, O.P.; Kumar, Anil (Indian Journal of Agroforestry, 2020)
In changing scenario of health consciousness, people give priority to organically produced fruits and vegetables; and that’s why vermicompost being an important organic source of plant nutrition, is widely used. Present study was conducted in newly established orchard (three-years old) to assess effect of different doses of vermicompost on growth and production of ber (Zizyphus mauritiana Lam.) cv. Seo and soil health. The experiment comprised of four treatments (T1- 1 kg, T2- 2 kg, T3- 3 kg vermicompost plant and T4- control) and seven replications under randomized block design. Plant growth and yield attributes were recorded. Soil samples were drawn before and after application of vermicompost and analyzed. Varying doses of applied vermicompost had no significant effect on plant height and collar diameter. However, incremental height and collar diameter differed significantly. T2 produced maximum fruit yield (3.45 kg plant-1) while it was minimum in T1 (2.39 kg plant-1). Average fruit weight was maximum in T2 (18.09 g) and minimum in T4 (15.06 g). After application of Â vermicompost, significant variations in soil pH, EC, soil organic carbon (SOC), available nitrogen (N) and dehydrogenase activity (DHA) were recorded. Maximum SOC, N and DHA were gained in soils of T3, followed by T2 and T1. Significant correlation existed between doses of vermicompost and available N (r= 1.000; P<0.005) and DHA (r= 0.954; P<0.005). Conclusively, it can be deduced from the study that use of vermicompost @ 2 kg plant-1 applied repeatedly for three months in the initial stage of ber, yields maximum fruits and also maintains soil health for sustainable production.